2018
DOI: 10.1111/cup.13118
|View full text |Cite
|
Sign up to set email alerts
|

The pathological spectrum and clinical correlation of pigmented purpuric dermatosis—A retrospective review of 107 cases

Abstract: This study described the wide pathological spectrum of pigmented purpuric dermatosis among Asians. Physicians should be aware about the clinical and pathological variations to facilitate diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 29 publications
2
48
0
3
Order By: Relevance
“…In a recent retrospective review of 107 Asian cases, five histopathologic patterns were observed: lichenoid (42%), perivascular (37%), interface (10%), spongiotic (7%), and granulomatous (4%). Of interest, lymphocytic vasculitis was noted in 16% of cases [116]. Schamberg, eczematoid, and lichen aureus clinical variants correlate with perivascular, spongiotic, and lichenoid histopathologic patterns [116].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recent retrospective review of 107 Asian cases, five histopathologic patterns were observed: lichenoid (42%), perivascular (37%), interface (10%), spongiotic (7%), and granulomatous (4%). Of interest, lymphocytic vasculitis was noted in 16% of cases [116]. Schamberg, eczematoid, and lichen aureus clinical variants correlate with perivascular, spongiotic, and lichenoid histopathologic patterns [116].…”
Section: Discussionmentioning
confidence: 98%
“…Of interest, lymphocytic vasculitis was noted in 16% of cases [116]. Schamberg, eczematoid, and lichen aureus clinical variants correlate with perivascular, spongiotic, and lichenoid histopathologic patterns [116].…”
Section: Discussionmentioning
confidence: 98%
“…However, differentiating MF from inflammatory dermatoses can be difficult in some cases [2,3]. Pigmented purpuric dermatosis (PPD) encompasses a group of cutaneous diseases that feature petechial and/or purpuric lesions [4], usually involving the legs. The disease can have several clinical subtypes [5] and may be related to various systemic diseases such as lupus erythematosus, lymphoid malignancies and rheumatoid arthritis [4,6,7], as well as medications such as ACE inhibitors, beta-blockers, antidepressants and calcium channel blockers [8].…”
Section: Discussionmentioning
confidence: 99%
“…In such circumstances, clinical involvement confined to the legs, presence of a CD8+ infiltrate shown with immunohistochemistry, as well as polyclonal TCR rearrangement can be helpful. However, some cases with a monoclonal TCR rearrangement have been described in the literature [4,6,7], as well as cases with partial loss of pan-T cell markers and CD4 expression [7]. The above-mentioned cases are commonly observed in patients with drug-related PPD [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation